2023
DOI: 10.3390/toxins15020104
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Different Yeast Cell Wall-Based Mycotoxin Adsorbents Using a Model- and Bioassay-Based In Vitro Approach

Abstract: Frequently reported occurrences of deoxynivalenol (DON), beauvericin (BEA), and, to a lesser extent, ochratoxin A (OTA) and citrinin (CIT) in ruminant feed or feedstuff could represent a significant concern regarding feed safety, animal health, and productivity. Inclusion of yeast cell wall-based mycotoxin adsorbents in animal feeds has been a common strategy to mitigate adverse effects of mycotoxins. In the present study, an in vitro approach combining adsorption isotherm models and bioassays was designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…Adsorptive properties for mycotoxins primarily occur from the β-D-glucan network present in the yeast cell wall which can generate multiple van der Waals and hydrogen bonds with mycotoxins. Research has shown YCWE to have adsorptive properties for numerous mycotoxins including but not limited to AFB1, DON, T2, FUM, ZEA, emerging mycotoxins, and Penicillium mycotoxins [ 11 , 14 , 38 ]. Recently, two meta-analyses have been published demonstrating the use of YCWE during mycotoxin challenges for broilers and growing pigs [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adsorptive properties for mycotoxins primarily occur from the β-D-glucan network present in the yeast cell wall which can generate multiple van der Waals and hydrogen bonds with mycotoxins. Research has shown YCWE to have adsorptive properties for numerous mycotoxins including but not limited to AFB1, DON, T2, FUM, ZEA, emerging mycotoxins, and Penicillium mycotoxins [ 11 , 14 , 38 ]. Recently, two meta-analyses have been published demonstrating the use of YCWE during mycotoxin challenges for broilers and growing pigs [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yeast cell wall proteins most often occur in the form of glycoproteins, mainly in its outer layer [ 25 ]. The mentioned cell wall polysaccharides and proteins are important for mycotoxin binding by yeast-based adsorbents [ 26 ]. The structural components of the A. pullulans cell wall are similar to those described for S. cerevisiae , which is the best known yeast in this regard [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 In order to characterize the mathematical relationship between adsorption capacity and adsorption conditions and analyze the microscopic mechanism of gas adsorption, The Freundlich adsorption equation was used for characterization, and its expression is shown as eqn (2): y = ax bx (− c ) where y is the adsorption capacity, a and b are the adsorption coefficients and c is the power parameter. 19 The range of application of this equation is wider than that of the Langmuir equation, which is suitable for a calculation of inorganic small molecule adsorption like CO. 20,21…”
Section: Methodology and Theorymentioning
confidence: 99%
“…where y is the adsorption capacity, a and b are the adsorption coefficients and c is the power parameter. 19 The range of application of this equation is wider than that of the Langmuir equation, which is suitable for a calculation of inorganic small molecule adsorption like CO. 20,21 Other than that, to better reveal the diffusion law of CO in the coal gangue and to assess the diffusivity of CO in coal gangue slit structures, the MSD and Einstein equations have been used to calculate the self-diffusion coefficient of CO in coal gangue models. This diffusion property is closely related to the type of material, diffusion medium and applied conditions.…”
Section: Simulation Theorymentioning
confidence: 99%